Social Media Activation Strategy pada Produk Olahan Kelapa Kopyor “Kosudu” - Febriani, Alifia; Rochdiani, Dini; Rachmawati, Erna; Djuwendah, Endah (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2024)
Coconut is a prospective plantation commodity. Many coconuts are further processed into various processed products, one of which is frozen coconut kopyor. This research aims to determine the implementation of brand activation and determine which social media activation strategy to be implemented in "Kosudu" frozen kopyor coconut. This research was designed with a case study approach in the Unit Usaha Kopyor Bogor. The informants and respondents were chosen through purposive sampling with criteria. The informants were 7 employees who provided information regarding “Kosudu”, while the respondents were 10 consumers who purchased the product. The analysis used in this research is SWOT and QSPM analysis. The research results show the implementation of the "Kosudu" social media activation, there are 8 activities in social media. The brand activation strategy for the Kopyor Bogor Business Unit is (1) Video advertisement (2) User Generated Content (3) Live dan post feed (4) Podcast.